2017
DOI: 10.1111/pre.12177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indole‐3‐butyric acid on growth, pigments and UV‐screening compounds in Nostoc linckia

Abstract: In the present research, the effect of indole-3-butyric acid (IBA) on the growth, and the production of some primary and secondary metabolites was studied in Nostoc linckia. In this respect, algae cultures were supplied with 0, 0.01, 0.1, 1, 10, and 100 μM IBA for 14 days. IBA at concentrations of 10 and 100 μM induced algal growth expressed as fresh weight in N. linckia. Treatment with IBA at all concentrations stimulated heterocyst formation. In addition, low concentrations of IBA (0.01, 0.1, and 1 μM) had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
1
5
1
1
Order By: Relevance
“…Also, auxin treatment caused an increase in the fresh weight on Nostoc. linckia algae; and the result was consistent with results of the present study (Mansouri and Talebizadeh 2017). As seen in the cultures treated with colchicine 0.5%, the cell division rate decreased in the culture that could be the reason for reduction of fresh and dry weights of algae (Soltani Nezhad and Mansouri 2019).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Also, auxin treatment caused an increase in the fresh weight on Nostoc. linckia algae; and the result was consistent with results of the present study (Mansouri and Talebizadeh 2017). As seen in the cultures treated with colchicine 0.5%, the cell division rate decreased in the culture that could be the reason for reduction of fresh and dry weights of algae (Soltani Nezhad and Mansouri 2019).…”
Section: Discussionsupporting
confidence: 94%
“…In this parameter, the enhancement effect of hormones on polyploidy created by colchicine could be seen, especially at 1 and 10 µM of hormones. Mansouri and Talebizadeh (2017) reported that low concentrations of IBA increased chlorophyll a , total chlorophyll and carotenoid content in Nostoc. linckia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanobacteria are a promising renewable source of bioactive secondary metabolites can be biotechnologically and commercially exploited in several ways (Mansouri & Talebizadeh 2017). Moreover, their growth, survival, MAAs and scytonemin production, pigmentation, nitrogen fixation, phycobilisome assembly, and carbon uptake have been shown to be affected by some abiotic factors such as different wavelength bands of UV radiation, desiccation, nutrients and salt concentration (Sinha et al 2003;Rastogi & Incharoensakdi 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are many relates to phytohormone supplementation in the cultivation of eukaryotic microalgae genres as Chlorella [11][12][13][14][15][16] and Scenedesmus [15,17,18]. Nevertheless, there are fewer studies about the use of this strategy to increase the cyanobacteria biomass [19][20][21], and it was found just one with Spirulina [22]. Spirulina is the most known cyanobacteria and one of the most-studied microalgae in the world [1].…”
Section: Introductionmentioning
confidence: 99%